E o caçador de marajás tinha pés áe barro ... ascensão e queda de Fernando Collor de Mello nas páginas da imprensa : O Globo e O Estado de S. Paulo (1987-1992) - Luz, Thaíze Ferreira da (2021)
The press deserves a prominent role during the democratic transition after the authoritarian period implemented in Brazil with the civil military coup of 1964, especially in the first presidential election and its aftermath. The 1980s represented a strategic moment in the organization of the Brazilian press, whether due to the changes introduced in the profile of journalism professionals and the role that newspapers and magazines began to play mainly in the political processes that took place in the country, as well as in the significant change in nature professional of the Brazilian press and in the relationship between media and politics. Thus, with this work we seek to problematize the thesis that the “press makes and unmakes a president”, analyzing the participation of other agents that emerged in the political scene in the pre-election period of 1989 and during the Collor government and how they influenced in this process. For this reason, based on the study of the Rio newspaper O Globo and the São Paulo periodical O Estado de S. Paulo, to verify how they approached the politician Fernando Collor de Mello since his electoral campaign for the presidency and later during his government. Thus, we seek to show how the two newspapers present themselves as legitimate in participating in the political debate of the time, as well as highlighting some elements that, in our opinion, need to be appreciated during the election process and the fall of the first president of the Republic of that period, elected by the direct vote, Fernando Collor de Mello. It is undeniable the protagonism assumed by the great Brazilian press at that moment, in particular, by our research object. Therefore, we used content analysis as a methodology, thus finding convergent and divergent elements in the analyzed periodicals, which enabled us to understand the role of part of the press in this context.